Pacific salmon: status of stocks and prospects for the fishery - A. N. Makoedov; A. A. Makoedov (Известия ТИНРО)
Dynamics of the pacific salmon landing is reviewed. Mean registered domestic catch of these species was about 175,000 t per year in 1925–2021, but taking into account other estimations, as the volume of Japanese fishery, at least 250 . 103 t of salmon spawned in the Russian waters (within present-day borders) were withdrawn annually in this period. The potentially maximum annual catch of the Russian-originated pacific salmon is estimated around 350 . 103 t. Under current conditions for the Russian fishery, the annual catch of pacific salmon is unlikely to be less than 140–150 . 103 t in low-productive years and less than 220–250 . 103 t in high-productive years. For the next decade, annual catch of pacific salmon will supposedly exceed these thresholds in 100–120 . 103 t.